Liquid chromatography/tandem mass spectrometric characterization of Rhodotorula mucilaginosa GMM natural pigment and its synergistic antitumor effect with γ-radiation: in-vitro and in-vivo study - Ghada S. Ibrahim; Amal I. Hassan; Manal G. Mahmoud; Mohsen M.S. Asker; Mohamed Marzouk (Journal of the Arab Society for Medical Research)
Background/aim Recently, there has been a marked increase in interest toward using microbial resources, especially yeast, to synthesize carotenoids. Ovarian cancer is a major health problem worldwide, as it is the most frequently diagnosed form of cancer in women and contributes significantly to cancer-related deaths. Yeast carotenoids are currently under evaluation for cost-effective and nonhazardous drugs derived from natural products. The principal objective of this study is to evaluate the natural pigment produced from Rhodotorula and characterize it by liquid chromatography-mass spectrometric and to evaluate the ability of its synergistic antitumor effect with γ-radiation. Materials and methods A new pigmented yeast was isolated from yogurt and identified. The pigment was characterized and studies of its biological activities were conducted. The isolate was defined as Rhodotorula mucilaginosa GMM with accession number OQ120277 by 18 S rDNA, and the pigment was characterized by liquid chromatography-mass spectrometric. Combining γ-radiation with a carotenoid pigment was also tested for its synergistic anticancer properties in CAOV-3 and HEK-293 cell lines and in experimental mice bearing solid tumors. BAX, BCL2, P53, MMP2, MMP9, caspase-3, and caspase-9 were measured using ELISA techniques. Results The maximum production of total carotenoids was 2.99 g/l. Pigment extract constituents exhibited 12 major compounds during its identification. Their structures can be sorted as 8 tetra, and 3 triterpenoidal carotenes (astaxanthin, 4,4’-E-diapophytoene, torularhodin, 1,2,1’,2’-tetrahyroxylycopene, E-β-apo-8’-carotenal, 10’-apo-E-β-caroten-10’-ol, β-carotene, torulene, echinenone, 1,2,1’,2’-tetrahyroxy dihydrolycopene, and α-canthaxanthin). The pigment exhibited DPPH scavenging activity, and the combination of natural pigment and radiation therapy showed a significant reduction (P<0.05) in the levels of matrix metalloproteinases (MMP2, MMP9), and significant increases (P<0.05) in the levels of tumor protein p53, Bax and caspases-3 and caspases-9 in CAOV-3 cell lines and mice bearing solid tumors. Conclusion The natural pigment produced by yeast fermentation in this study exhibited a potential antitumor efficacy when combined with radiation in cell lines and against Ehrlich solid tumors.